The Effect of Leverage, Liquidity, Profitability, Firm’s Growth, Firm’s Size, and Dividend Policy toward Firm Value (Study at Manufacture Companies Listed on Indonesia Stock Exchange Period 2014-2017) - Ade Irma Anggraeni; Ade Banani (Jurnal Akuntansi, Manajemen dan Ekonomi, 2021)
This study aims to analyze the leverage (DER), liquidity (CR), profitability (ROE), firm growth (sales growth), firm size (Ln Total Asset), and dividend policy (DPR) on firm value (PBV) at manufacturing company listed on the Indonesia Stock Exchange for the period of 2014 – 2017. The population in this study were 177 companies. The sample used in this study were 10 companies. Sample were taken by purposive sampling method. Data in this study were analyzed with multiple linear regression. The result showed that leverage (DER) has negative and significant on firm value (PBV), liquidity has no effect on firm value (PBV, profitability (ROE) has positive and significant effect on firm value (PBV), firm growth (sales growth) has positive and significant effect on firm value (PBV), firm size (Ln of total asset) has positive and significant effect on firm value (PBV), and dividend policy (DPR) has no effect on firm value (PBV).